Situation Report: Bulgaria, 12 March 1970 - Radio Free Europe/Radio Liberty Research Institute (RFE/RL Research Institute)
An information bulletin produced by Radio Free Europe based on extensive monitoring of communist bloc news outlets and primarily intended for internal circulation. Pieces were generally contributed by the staff of the research and analysis departments and treated current affairs in the region. Todor Zhivkov Visits Vratsa Again New Figures on 1969 Foreign Trade Reported Economic Relations with Balkan Nations Concentration of Foreign Trade Enterprises Reorganization of Foreign Trade Enterprises Reorganization of Bulgarian Civil Aviation Bulgaria Postpones PEN Meeting Party Delegation to UAR